Can visual language convey tactile experience? A study of the tactile compensation effect of visual language for online products - Leng, Xionghui; Zhou, Xiaoyu; Wang, Shuting; Xiang, Yibin (Frontiers in Psychology, 2022)
Introduction There is a common phenomenon of tactile missing in online retail. How to realize consumer tactile compensation is a consensus problem in the field of e-commerce. More and more marketeers and scholars convey their ideas via visual display, but few researches have focused on the tactile compensatory effect of visual language. Methods Study 1 collected data from nearly 13,000 online purchases to analyze the impact of haptic cues on sales in real online shopping platforms; Study 2 used a experimental research method to design three experimental groups: hand haptic cue group vs. Object haptic cue group vs. control group (N = 165) to investigate whether the main effect of haptic cues and the dual mediating effect of mental simulation held. Study 3 also adopted a simulated experimental research approach to design a two-factor group: 2 (haptic cue: hand vs. object) × 2 (product type: tactile functional product vs. tactile experiential product) (N = 198). To further explore whether the moderating effect of product type holds based on Study 2. Results Therefore, based on the visualization theory and mental simulation theory, and through a second-hand data experiment and two simulated experiments, this study confirmed that visual language did have a compensation effect on tactile missing specifically. Haptic cues in metaphorical visual language can actively compensate for consumers’ tactile loss, thus affecting the purchase intention. Mental simulation plays a mediating role in the tactile compensation effect. Product type has a moderating effect, and the use of hand (object) haptic cues in metaphorical visual language in tactile functional products (tactile experiential products) can lead to a more active purchase intention. Discussion This study not only enriches the theoretical research on the tactile compensation effect of visual language, but also provides valuable management enlightenment for e-commerce enterprises to improve the effectiveness of online product display and online sensory marketing strategies.